Avaliação comparativa entre o efeito anticoagulante de Fosfolipases A2 isoladas de peçonhas de serpentes dos gêneros Bothrops e Crotalus e fármacos anticoagulantes - Oliveira, Pierri Emanoel de Abreu (2022)
The prevalence of snakebites is a public health problem that causes significant impact economically and socially. In South America, Brazil has the highest recorded rate of snakebites, with approximately 29,000 cases per year. Of the components that play a central role in the symptomatology of snakebites, phospholipases A2 (PLA2s) acts on substrates by hydrolyzing biomembranes phospholipids. Coagulation occurs by the activation of clotting factors together with calcium and platelets, and these factors are possible targets for PLA2s to act. In the present study, the pharmacological effects of PLA2s from Bothrops and Crotalus snake venom on secondary hemostasis were evaluated and a probable mechanism of the anticoagulant action of these proteins was proposed. In vitro, Prothrombin Time (PT) and Partial Thromboplastin Time (PTT) of citrated human plasma samples were evaluated in the presence of different quantities of the five anticoagulant drugs or the PLA2s. None of the evaluated PLA2s caused significant PT prolongation, while the aPTT demonstrated significant changes caused for all PLA2s. Asp49-PLA2s basic (bothropic) were classified as strong anticoagulant; Asp49-PLA2s acidic (bothropic) and basic (crotalic) were weak anticoagulant; while all Lys49-PLA2s were moderate anticoagulant. In silico studies, multiple alignment, phylogeny and interaction between PLA2s and Factors IXa and Xa were performed. In conclusion, PLA2s can interfere in the coagulation cascade by three independent mechanisms, or a combination of them: i) inhibition of the tenase complex formation observed in Asp49-PLA2s basic (bothropic) and Lys49-PLA2s. These PLA2s interact with the B subunit of factors IXa or Xa, which may cause a steric hindrance; ii) allosteric modulation of Factors IXa and Xa induced by the interaction of Lys49-PLA2s through the C-terminal region, iii) phospholipids hydrolysis and/or competition of catalytically active PLA2s with the clotting factors for the lipid surface.